Fibrinogen concentrate for treatment of bleeding and surgical prophylaxis in congenital fibrinogen deficiency patients. (21st January 2020) - Lissitchkov, Toshko; Madan, Bella; Djambas Khayat, Claudia; Zozulya, Nadezhda; Ross, Cecil; Karimi, Mehran; Kavakli, Kaan; De Angulo, Guillermo R.; Almomen, Abdulkareem; Subramanian, Kannan; D'Souza, Fulton; Viswabandya, Auro; et al.
Abstract: Background: Congenital fibrinogen deficiency is an ultra‐rare disorder in which patients can experience severe and/or frequent bleeding episodes (BEs). Here, we present the largest prospective study to date on the treatment of this disorder. Methods: Hemostatic efficacy of human fibrinogen concentrate (HFC; FIBRYGA ®, Octapharma AG) for treatment of bleeding or surgical prophylaxis was assessed by investigators and adjudicated by an independent data monitoring and endpoint adjudication committee (IDMEAC) according to a four‐point scale, using objective criteria. Thromboelastometry maximum clot firmness (MCF) was also determined. Results: Twenty‐five afibrinogenemia patients were treated with HFC: 24 for on‐demand treatment of 89 BEs, and nine as prophylaxis for 12 surgeries. For BEs, treatment success (rating of excellent or good) evaluated by investigators was 96.6% (90% confidence interval [CI], 0.92‐0.99; two missing ratings, classified as failures) and by the IDMEAC was 98.9% (90% CI, 0.95‐0.999). Mean ± standard deviation (SD) increase in MCF was 5.8 ± 2.5 mm one hour after the first HFC infusion (mean ± SD dose, 61.88 ± 11.73 mg/kg). For the 12 surgeries (median [range] HFC dose/surgery, 85.80 mg/kg [34.09‐225.36]), intraoperative and postoperative treatment success were both rated 100% (90% CI, 0.82‐1.00) by investigators and the IDMEAC. Three adverse events were possibly treatment related, including a moderate case of thrombosis. There were no deaths, no severe allergic or hypersensitivity reactions, and no clinical evidence of neutralizing antifibrinogen antibodies. Conclusions: Human fibrinogen concentrate was efficacious for on‐demand treatment of bleeding and as surgical prophylaxis, with a favorable safety profile, in patients with congenital afibrinogenemia.